Using Quantitative Sociological Methods for Functional Analysis of Academic Libraries - Landoy, Ane; Ghinculov, Silvia; Repanovici, Angela; Cheradi, Natalia (Qualitative and Quantitative Methods in Libraries; Vol 7 No 2 (2018): June 2018 Issue, 2019)
In this article the authors present the study of assessing the needs of academic libraries modernization was conducted within the framework of the project "Modernization of academic library services in Moldova" carried out during October 2016 - May 2017 with the financial support from the Norwegian Centre for International Cooperation in Education (SIU). In the course of the assessment study 25 managers of academic libraries from the Republic of Moldova formed a working team to train on strategic planning, to evaluate the activity of academic libraries, as well as to provide a methodological support for the formulation of their own Development Strategies. In order to facilitate the development of strategies there was hired a specialized company which carried out a functional analysis, operational and institutional capacity assessment and guided the development of strategic plans for academic libraries by organizing focus groups and online or informal interviews. With the help of the Institute of Legal and Political Research of the Academy of Sciences of Moldova there was carried out a quantitative sociological research that determined the development trends of academic libraries over the long run under the conditions of the competitive information environment. The assessment study results that reflected the views of both library managers and the users of their services served as an empirical basis for the development of strategic documents. The novelty of the study is a planning exercise done for the whole network of libraries, based on the study of the needs for modernization carried out by the experts outside the library domain. The method used can be replicated for other libraries networks that develop strategic plans in the new technological and economic context.